ISLAM STATE AND POLITICS IN ISLAMIC POLITICAL DISCIPLINE - Amirudin, Amirudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Historical reviews and analyses of the relationship between Islam, the state and politics are always interesting to discuss. A historical review would be significant for the discussion to show that an understanding of secularism, for example, is not a foreign idea in the history of Islamic societies. The purpose of this study is to provide confirmation that Islam does not only talk about worship. Islam is political and stately, the confidence of Islam in politics and state is proven based on historical facts and civilizations that are carved closely. This research is a literature research with a historical approach, so the data presented is the result of historical literature analysis. The results of the study explain that there is a separation between religious and political authority that can be traced back to the time of Abu Bakr as the first caliph of the state of Medina. The fact that this view does not prevail among Muslims does not mean that this view is in itself wrong. In fact, the crisis in relations between Islam and the state and politics that Muslims are experiencing today wherever they are, indicates the need for a new way of reading history. The conclusion of this study is that it is clear that the models of relations between religious authorities and the state vary from heightened state control over central religious institutions to more independent but cooperative relations, and full autonomy and even open opposition to state policies.